1989
DOI: 10.1007/bf01957472
|View full text |Cite
|
Sign up to set email alerts
|

Latent iron deficiency alters gamma-aminobutyric acid and glutamate metabolism in rat brain

Abstract: A diet containing 18-20 mg iron/kg to young weaned rats for 8 weeks altered the metabolism of gamma-aminobutyric acid and glutamate in the central nervous system without affecting blood hemoglobin. Subsequent rehabilitation with 390 mg iron/kg diet for 2 weeks normalized these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…These broader effects in the dietary model might have been due to the secondary effects of IDA rather than direct effects of ID. Our results are consistent with studies linking dietary ID after weaning with decreased brain glutamate concentrations (53,54). Iron levels regulate central nervous system glutamate formation and secretion via the iron-dependent enzyme cytosolic aconitase (IRP-1) in retinal pigment epithelial cells (55).…”
Section: Discussionsupporting
confidence: 93%
“…These broader effects in the dietary model might have been due to the secondary effects of IDA rather than direct effects of ID. Our results are consistent with studies linking dietary ID after weaning with decreased brain glutamate concentrations (53,54). Iron levels regulate central nervous system glutamate formation and secretion via the iron-dependent enzyme cytosolic aconitase (IRP-1) in retinal pigment epithelial cells (55).…”
Section: Discussionsupporting
confidence: 93%
“…Lozoff et al found that children with severe, chronic ID in infancy had a greater prevalence of anxiety, depression, and attention problems [40]. Some animal studies have shown an association between IDA and alterations in serotonin, norepinephrine, and gamma-aminobutyric acid (GABA) neurotransmission [21,61]. In assessing weanling rats with either an iron deficient diet or a control diet for 6 weeks, Beard et al found reduced activity and increased anxiety-like behaviors among the iron deficient rats with significant decrements in brain iron content in the corpus striatum, prefrontal cortex, and midbrain [62].…”
Section: Discussionmentioning
confidence: 99%
“…An inverse correlation between extracellular GABA and Fe concentrations was also observed, with GABA concentration increasing with decreased Fe, suggesting that decreased Fe (due to both dietary deficiency and Mn-exposure) affects the levels of extracellular GABA. Iron deficiency affects GABA synthesis via glutamate decarboxylase (GAD) (Li, 1998) and a reduction in GABA brain tissue concentrations has been shown in rats fed a marginally ID diet for eight weeks (Shukla et al, 1989). Low tissue neurotransmitter levels may be the result of decreased uptake of the respective neurotransmitter (Gainetdinov et al, 1998), increasing the extracellular concentrations, a scenario which might be occurring in the current study.…”
Section: Discussionmentioning
confidence: 99%